THE GOVERNMENT'S ROLE IN IMPROVING THE QUALITY OF MSME PRODUCTS IN SEPANDE VILLAGE - Aurandhi Sp , Alnesta; Rodiyah, Isnaini (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze and describe the role of the government in improving the quality of MSME products in Sepande village. Method: The research method used uses a qualitative method. This research was carried out in Sepande Village, Sidoarjo District, Sidoarjo Regency. The focus of the research is to analyze the role of the government, this role is divided into 5 indicators, namely l) Regulator, 2) Facilitator, 3) Dynamizer, 4) Protector, 5) Promoter. Data collection techniques use interviews, observation and documentation, data analysis using qualitative descriptive analysis.  Results: The results of the study concluded that the Government of Sidoarjo Regency and Sepande Village has tried to carry out its role as regulators, facilitators, dynamizers, protectors, and promoters through various programs such as "I Love Sepande MSMEs", product certification programs, digitization of MSMEs, the formation of cooperatives, and the MSME Expo.  Novelty:  Development of a comprehensive government role evaluation framework with five specific indicators (regulators, facilitators, dynamizers, protectors, and promoters) that are applied in-depth in the context of tourism villages with unique characteristics as "1000 MSME Villages", where there has been no previous research that analyzes these five roles simultaneously and integrated in specific geographical and demographic settings such as Sepande Village.